A history of Chinese theatre in the 20th century. IV - Fu, Jin, 1956-; Zhang, Qiang (Translator) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
The 20th century was a dynamic period for the theatrical arts in China. The four volumes of A History of Chinese Theatre in the 20th Century display the developmental trajectories of Chinese theatre over those hundred years. This volume examines the development of Chinese theatrical art from the Cultural Revolution to the end of the 20th century. The Cultural Revolution had a devastating influence on the theatrical profession, reducing the creation of performance art to serving the political authorities. Adopting a critical view, the author argues that the Reform and Opening-up of the late 1970s not only ended this period of political interference, but also brought about chaos and doubts to the theatrical circle, since neither tradition nor western concepts were a panacea for the problems faced by Chinese theatre.Heposits that people should advocate patterns of drama that are rich and colourful in their expression while encouraging the coexistence and competition of different artistic concepts. Scholars and students in the history of the arts, especially the history of Chinese theatre, will find this book to be an essential guide.
"English version by permission of China Social Sciences Press"
Keywords: Theater -- China -- History -- 20th century; Chinese drama -- 20th century -- History and criticism; PERFORMING ARTS / Theater / History & Criticism; ART / Asian; ART / History / General